Paramedic point of care ultrasound at Australian mass gatherings. Issue 1 (19th February 2019) - Baron, Aidan; Beirne, Gerrie; Wald, Anthony
Abstract: Point of care ultrasound (POCUS) is not traditionally performed by paramedics, and where it is used, is generally limited to resuscitative‐type ultrasound examinations. We describe a select series of patient care cases collected between August 2017 and February 2018 which are the first known examples of expanded POCUS performed by a paramedic in this context. These point of care scans were performed for both high and lower acuity patient presentations and are felt to have contributed to improved decision‐making in the treatment and onward referral of patients in the Australian festival and event medicine.